Pemberian Complementary and Alternative Medicine pada Pasien Kanker - Tifany Hayuning Ratri; Abu Bakar; Ni Ketut Alit Armini (Jurnal Keperawatan Silampari, 2022)
This study aims to analyze the effect of giving Complementary and Alternative Medicine (CAM) to cancer patients. The method used is a systematic review using three databases: PubMed, Science Direct, and Google Scholar. The results showed that of the fourteen articles reviewed, thirteen articles showed that the use of Complementary and Alternative Medicine (CAM) could reduce the side effects of chemotherapy, increase self-confidence in physical, social, and body image functions, provide satisfaction with life, and reduce anxiety. , positive quality of life enhances hereditary resistance, improves well-being, and overcoming the disease. One article states that CAM users report more severe anxiety and skin or hair changes.In conclusion, some types of CAM have beneficial effects for some clients. Still, on the other hand, there are adverse effects without the client realizing that this therapy can be a source of chemicals that can interact with conventional drugs. Monitoring the patient's treatment consumption is necessary to avoid these side effects. Keywords: Alternative Medicine, Cancer Cell, Cross-Sectional, Complementary therapy, Quality of Life